Knowledge regarding diarrhoea prevention and its management and its determinants among mothers of under 5 age children in urban area of Sangareddy, Telangana - Abida, Humera; Gilla, Sravanthi (International Journal Of Community Medicine And Public Health, 2019)
Background: Diarrhoea is the second leading cause of death in children under five years of age, and is responsible for killing around 5,25,000 children every year. A major determinant of child health is the health and knowledge of the mother. So the knowledge, attitude and health practices of the mothers directly reflect on the health and vitality of the child. Methods: A community based cross sectional type of study was conducted among mothers who had children of 0-5 years of age using pre designed, pretested structured questionnaire. Study area was 5 urban slum pockets in Tertiary care hospital of Sangareddy, Telangana. 255 mothers were selected for the study using random sampling technique. Results: Out of the total 255 study populations most of the mothers were literate, living in nuclear families belonging to Hindu religion. About half of the mothers had knowledge regarding diarrhoea and 71.4% of the mothers have given hospital treatment for it. When asked about 78.4% of mothers told that they follow preventive health practices. Majority of mothers had a good knowledge regarding steps to be taken by health care facility during diarrheal attack. Conclusions: On the basis of the present study, there was a significant association of knowledge regarding diarrhoea with maternal literacy and socio economic status. This study brought out the health seeking behaviour of mothers of under five children.